Gambaran Kepuasan Pasien terhadap Pelayanan Keperawatan di Ruang Rawat Inap Rumah Sakit XYZ Tahun 2009 - Marpaung, Bintang Sahala (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2010)
XYZ Hospital has service facilities: early detection integrated diagnostic unit, radiotherapy, descending immunity isolation room, wound and polyclinic of wound and short nursing. Satisfaction is comparison result between hope and fact gotten by patients from nursing service. Globalization demands nursing service must be able to present qualified and satisfied service. The research goal is to find out a brief illustration of patientsâ satisfaction in opname room at XYZ Hospital and to find out correlation between five dimensions of service quality and patientsâ satisfaction. The research method is quantitatively by cross sectional approach to the patients of VVIP, IP, class-1, class-2, and class-3 in chemotherapy, radiation, and operation programme. Data collection mechanism is by means of questionnaire with random sampling method. Based on the research to 57 patients, it can be obtained data as follows: most respondents feel satisfied (63,2%) and the rests do not feel satisfied (36,8%). Reliablity data shows 37 respondents (64,9%) feel satisfied and 20 respondents (35,1%) do not feel satisfied. Responsiveness data shows 32 respondents (56,1%) feel satisfied and 25 respondents (43,9%) do not satisfied. Emphaty data shows 36 respondents (63,2%) feel satisfied and 21 respondents (36,8%) do not feel satisfied. Assurance data shows 39 respondents (68,4%) feel satisfied and 18 repondents (31.6%) do not satisfied. Keywords: Clientsâ satisfaction; Service quality.